Liquid fuel sloshing control of an automotive fuel tank. (July 2019) - He, Yirong; Zeng, Zhixin; Yu, Yanglei; Ruan, Dengfang
In order to reduce the influence of fuel sloshing on the interior noise of a passenger car, the fuel tank sloshing noise was first evaluated with a subjective evaluation method to determine the driving cycle of the car and the fuel filling percentage of the fuel tank in which the fuel tank sloshing noise is serious, and then two anti-wave boards with different structural characteristics were designed to reduce the fuel sloshing. On this basis, fuel sloshing in the fuel tank equipped with the newly designed and original anti-wave boards was simulated numerically; then, the anti-wave board with the best effect of inhibiting fuel from sloshing was selected based on the numerical results; finally, the anti-sloshing effect of the selected board was evaluated through the car road test. The test results show that the vibration acceleration magnitude at each monitoring point of the tank with the selected anti-wave board is significantly reduced compared with the original fuel tank, which indicates that the selected anti-wave board inhibits fuel from sloshing greatly.